Catla 2023 G1 families - Hamilton, Matthew; Akhter, Md; Roy, Aashish Kumar; Sarkar, Uzzal Kumar; Kundu, Ramprosad; Shanta, Sirajum Monira; Rahman, Md. Mustafizur; Kamruzzaman, Md.; Hossain, Jamal; Haque, Mojammel; Hossain, Md.; Sarkar, Anutosh; et al. (2023)
Generation one families produced as part of the WorldFish Catla Genetic Improvement Program